Strategic anonymity and behavior-based pricing - Stefano Colombo; Paolo G. Garella; Noriaki Matsushima (Osaka University, Institute of Social and Economic Research (ISER), 2023)
In a model of behavior-based price discrimination (BBPD), we argue that sellers may have discretionary power to let buyers decide whether to be identified (e.g., creating an account) or remain anonymous (no account creation). The price equilibria generate a more fragmented market segmentation than under the standard BBPD. Firms might prefer a policy where they leave buyers the decision to remain or not be anonymous, breaking the standard BBPD result. Furthermore, firms can realize higher profits than under uniform pricing, contrary to the standard BBPD. Also, firms may adopt asymmetric policies concerning the account creation requirement.
Keywords: D43; L13; 330; strategic anonymity; behavior-based pricing; privacy